Taṣmīm Barnāmij Autoplay Fī Ta'līm Al-Lugah Al-'Arabiyyah Litarqiyyah Al-Mahārāt Al-Lugawiyyah Bimadrasah Wāhid Hāsyim As\-S\Ānawiyyah As\-S\Āniyyah Tāmān Sīdowārjo - Khanafi, Mukhammad (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2020)
The hope that never disappears and always demands the teacher is how the material delivered by the teacher can be mastered by students thoroughly, this is a pretty difficult problem felt by the teacher. The problem that occurs in the learning process at this school is that the material used is an Arabic conversation book which contains only all conversations and there are no text and practice questions. This makes students bored even though they learn Arabic by memorizing what is in the book, and students feel they need new material to be creative and innovative in their learning.With the autoplay application, it is hoped that it can increase interest and motivation to learn Arabic so they can succeed in learning. The research method used by researchers in this research is experimental quantitative method.From the results of the study that there is a high level of effectiveness and attractiveness based on learning outcomes in the post test 40% greater than the pre test, where the graduation rate at the beginning is 50% to 90%. Because the t value is greater than 13,887> 2,045 than the t table value, it means that there is an effect of using Autoplay in improving Arabic language skills in this school.So the researchers concluded that the use of autoplay media was very effective.